Relevance of the Morphological Concepts Root, Stem and Base in the Structural Analysis of Sinhalese Words. - Randula, K. K. G. (The Third International Conference on Linguistics in Sri Lanka, ICLSL 2017. Department of Linguistics, University of Kelaniya, Sri Lanka., 2017)
The term piyewi (prəkṛti) appearing in traditional Sinhalese grammars refers to an element operating within word structure. It is a morphological extraction which has not been properly defined in any of the traditional Sinhalese grammars. Therefore attempts have been made by some modern Sinhalese linguists to define pijewi (prəkṛti) with the light of morphology. However, the piyewis (prəkṛti) extracted by modern linguists are totally different from the piyewis (prəkṛti) extracted by traditional grammarians. This difference of the forms has resulted in much debate among Sinhalese scholars. The study was designed to identify the most appropriate morphological extraction which best suits the structural analysis of the Sinhalese words. Data for the study were collected from a number of grammatical works and linguistic works. It was observed that modern linguists have employed three slightly different morphological concepts as root, stem, and base in their morphological analyses. Just as the term piyewi (prəkṛti) in Sinhalese, they too refer to some abstract morphological element operating within the word structure. After examining the technical definitions of the three terms, a significant observations has been made: the notions of root and stem are similar to what is known as piyewi (prəkṛti) by traditional Sinhalese grammarians, while the notion of base is similar to what is known as piyewi (prəkṛti) by modern Sinhalese linguists. This study recognises stem as the best morphological extraction that fully facilitates the structural analysis of Sinhalese words. The concept of root can also be employed with a theoretical restriction only when referring to what is known as simple stem. The concept of base is not an appropriate selection as it produces a number of totally abstract extractions that even violate the syllabic structures of the Sinhalese language. It also makes the morphological analysis unnecessarily complicated. As evident from these facts, it is the use of the same term piyewi (prəkṛti) in referring to both stems and bases that has led the Sinhalese scholars to confusion. In order to avoid such confusions, this study proposes three distinctive Sinhalese terms as muːlə, prəkṛti and paːdəkə for root, stem, and base respectively.
Keywords: Abstract; Base; Extraction; Root; Stem